The Knowledge Spiral in Community of Practice: Teachers' Knowledge Transformation in Developing Innovative High School Science Curriculum - Meng-Yu Lin; Wu-Lung Chung; Yueh-Hsia Chang (National Taipei University of Education, 2015)
This study aims at investigating how knowledge spiral operates in a community of practice in which a group of vocational high school teachers developed innovative science curriculum for science courses. Research data for this qualitative study was obtained through interviews, direct participatory observation, and document analysis. Four modules of knowledge transformation model, including socialization, externalization, combination and internalization, are used to analyze each phase. The analysis shows how implicit knowledge is transformed into explicit knowledge and vice versa. The results also show that when knowledge spiral model is applied to an innovative curriculum development, the phase of developing experimental equipment can be a good starting point. For the development of the innovative curriculum, the curriculum community of practice went through four modes of knowledge transformation: socialization, externalization, combination, and internalization, in which each of the four modules possesses its own significance and the lack of any mode will result in setbacks in knowledge development. It is indicated in the findings that knowledge spiral starts off only after the community of practice have involved themselves in organizational learning and it works not only on individual teachers but also in the entire school organization.